Objective Longitudinal Measures of Physical Activity and Bone Health in Older Japanese: the Nakanojo Study. Issue 4 (9th December 2016) - Shephard, Roy J.; Park, Hyuntae; Park, Sungjin; Aoyagi, Yukitoshi
Abstract : Objectives: To examine dose/response relationships between habitual physical activity and bone health in the elderly. Design: Longitudinal. Setting: Community of Nakanojo. Participants: Community‐living Japanese aged 65 to 84 (212 men, 284 women). Measurements: Daily 24‐h pedometer/accelerometer data were collected continuously for 5 years. A quantitative calcaneal osteosonic index (OSI) was determined annually. Results: Year‐end OSI values were higher in those with greater daily step counts and especially a greater duration of activity >3 metabolic equivalents (METs). However, after controlling for baseline OSI, age and body mass, final OSI values were not significantly greater in the fourth than in the third activity quartile, where men and women, respectively, took means of 7, 700 and 7, 500 steps/day and/or exercised at an intensity >3 METs for means of 19 and 17 min/day. A multivariate‐adjusted proportional hazards model predicted that the OSI values of men and women were, respectively, 2.6 (1.4–4.4) and 3.3 (2.1–5.2) and/or 2.8 (1.5–5.6) and 3.9 (2.4–6.7) times more likely to drop below the OSI fracture threshold over 5 years in the two lowest activity quartiles (<7, 000 and <6, 900 steps/day and/or <18 and <17 min/day at >3 METs) than in the highest quartile (>9, 100 and >8, 800 steps/day and/or >30 and >25 min/day at >3 METs). Conclusion: After adjustment for potential confounders, the calcaneal health of seniors is associated with both the daily step count and the duration of activity at an intensity >3 METs. The bone health is optimal in elderly people who take at least 7, 000‐8, 000 steps/day and/or spend at least 15–20 min/day at an intensity >3 METs.